Morocco : Selected Issues. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Selected Issues paper studies the potential for well-sequenced labor and product market reforms to play a more important role in promoting growth and job creation in Morocco. A Dynamic General Equilibrium model is used to assess the macroeconomic effects of different reform scenarios (isolated, coordinated, or sequenced) that reduce hiring costs and/or firms' entry costs in the presence of a large informal sector. The paper highlights that reforms are most effective if executed in a coordinated fashion, as implementing simultaneous reforms in the labor and product markets could add about 2.5 percent of gross domestic product growth and reduce unemployment by about 2.2 percentage points after five years. If reforms are to be introduced sequentially, due for instance to capacity or political economy constraints, starting with product market reforms is more effective in boosting output in the short-run while starting with labor market reforms would reduce unemployment faster.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet